Provider Order Entry with Integrated Decision Support: from Academia to Industry - Giuse, D.A. (Methods of Information in Medicine, 2003)
Objectives: To describe the evolution of a provider order entry system with integrated decision support, from a research prototype to full implementation at one academic center, and finally to a commercial product.Methods: Describe the institutional environment and planning process in which the system originated. Highlight the historical evolution of the provider entry system, and analyze its system architecture and functionality. Describe the requirements for successful design and deployment both within a single health care organization and as part of a commercial product line.Results: Over a period of eight years the system evolved from a research prototype to a fully integrated order entry system in routine use on most inpatient units of a large academic medical center. Around 12,000 orders are entered every day into the computer system; 70% of those are entered directly by the responsible physician. The system embeds best-of-care practice guidelines, and is used to reduce resource utilization by limiting unnecessary testing and suggesting more effective or less costly therapeutic replacements. The system was recently acquired by a large HIS software vendor and is being rapidly implemented at numerous customer sites.Conclusions: Large-scale development or deployment of complex health information systems requires considerable organizational agreement and resources, as well as close attention to iterative system design that explicitly includes constant feedback from the user community. The transformation of such a system from a single-site success to a widely deployed product requires convergence of resources and needs.
Keywords: Clinical information systems; provider order entry with decision support; user-driven software design